“Dwelling Amid Ruins”: Hope, Lament, and Necropolitics - Jaiyesimi, Wemimo B. (Political theology, 2025)
This article inserts itself within the resurgence of interest in hope in recent work in theology, political theory, and moral psychology. It contributes to the discourse on how hope might be positioned as a virtue rather than a vicious orientation detrimental to the interests of the oppressed. In dialogue with the criticism of hope as privileged discourse, immobilizing of praxis, that social ethicist Miguel De La Torre makes, this article argues for lament as a crucial accompaniment for keeping hope from these dangers. To do this, the article draws upon and furthers Emmanuel Katongole’s innovative dyadic framing of lament and hope, making a case for how both intertwined virtues energize important political work in our necropolitical world.